Microstructural, tribological, and corrosion behavior of B4C-added TiO2 coatings applied on 316 L stainless steel via sol-gel method - Eraslan, Fatma Sezgi; Birol, Burak; Gecu, Ridvan (ELSEVIER SCI LTD, 2024)
Corrosion protection of metals is essential for a wide range of technological applications, and coating metal surfaces with protective materials is a commonly employed method to achieve this. Among these, TiO2 coatings are extensively used due to their excellent photocatalytic properties, their applications in sensing and solar cells, and enhancing the corrosion and wear resistance of metal surfaces. Recent advancements have focused on the incorporation of carbide particles, such as B4C, to further improve the performance of TiO2 coatings. In this study, TiO2 coatings containing 0-3.25 wt% B4C were applied to a 316 L stainless steel substrates using the solgel method. The coatings were characterized by XRD and SEM-EDS analyses, and their wear and corrosion properties were evaluated using ball-on-disc wear tests and corrosion tests in NaCl solutions. The results demonstrated that lower concentrations of B4C led to improved wear resistance, likely due to the formation of a durable tribolayer, while higher concentrations reduced the wear resistance, attributed to increased oxidation and the formation of brittle phases. Corrosion resistance was enhanced in coatings containing 0.25 wt% and 1.25 wt% B4C, which can be attributed to the formation of protective B2O3 phases. However, at higher B4C concentrations, the corrosion rate increased, primarily due to the presence of cracks in the coating structure. Overall, the addition of 0.25 wt% B4C to the TiO2 coating significantly improved wear and corrosion resistance, indicating its potential as an effective additive for protective coatings.
Keywords: TiO 2 coatings; B 4 C reinforcement; Sol-gel method; Corrosion; Wear resistance; COMPOSITE COATINGS; GAS SENSOR; LAYER; FILMS; PROTECTION; RESISTANCE; REDUCTION; OXIDATION; TIB2; Materials Science